On The Symbolic 2-Plithogenic Number Theory and Integers - Hamiyet Merkepci; Ammar Rawashdeh (Neutrosophic Sets and Systems, 2023)
The objective of this paper is to study for the first time the foundational concepts of number theory in 2-plithogenic rings of integers, where concepts such as symbolic 2-plithogenic congruencies, division, semi primes, and greatest common divisors. In addition, many elementary properties will be discussed in details through many theorems and examples.